Acculturation of Mandailing Culture and Minangkabau Culture in Paraman Ampalu, West Pasaman: A Study Of Social and Cultural Identity - Harijul Lubis; Syarbaini Saleh (MASI Mandiri Edukasi, 2026)
Cultural acculturation is a prominent phenomenon in multicultural societies, particularly in regions where different ethnic groups coexist over extended periods. In Indonesia, border areas often become spaces of intensive cultural interaction that shape social and cultural identity in complex ways. This study addresses the problem of how acculturation between Mandailing and Minangkabau cultures influences social identity formation in Paraman Ampalu, West Pasaman Regency. Although acculturation is often assumed to promote harmonious integration, differences in kinship systems and cultural dominance may result in asymmetrical adaptation. Therefore, this research aims to analyze the dynamics of Mandailing–Minangkabau acculturation and to examine how social identities are constructed and negotiated in everyday life. This study applies a qualitative research design using ethnographic methods. Data were collected through in-depth interviews, participant observation, and documentation involving community leaders, customary figures, religious leaders, and local residents. The results indicate that acculturation in Paraman Ampalu is a natural and dynamic process that does not eliminate cultural identity but produces a contextual and flexible social identity. Customary institutions serve as arenas for cultural negotiation, while shared Islamic values strengthen social cohesion and reduce potential conflict. Acculturation is most evident in daily social practices, particularly intermarriage, and the emergence of a shared local identity among younger generations. However, acculturation operates selectively, with minority groups often adapting to dominant cultural norms in public domains. This study contributes to a deeper understanding of cultural acculturation and social identity in multicultural societies and provides insights for inclusive cultural education and community-based policy development.